The Impact of Exchange Rate Fluctuations on Trade Flows in Algeria: An Econometric Analysis Using the ARDL Model - Samir , Haffaci; Imane , Zitouni (Future Science, 2025)
This study investigates the impact of exchange rate fluctuations on Algeria’s foreign trade flows (exports and imports) over the period 1995–2023. It employs the Autoregressive Distributed Lag (ARDL) model to capture both short-term dynamics and long-run equilibrium relationships. The relevance of this topic stems from the growing importance of understanding how currency volatility influences trade performance in the Algerian economy, particularly amid global economic uncertainty and recurrent monetary shocks. A descriptive-analytical approach is adopted, integrating econometric modeling to examine the interactions among key macroeconomic variables—namely, exchange rate, GDP, and inflation. The ARDL methodology facilitates a robust empirical framework, enabling the estimation of both immediate responses and long-term adjustments. The results reveal that GDP has a statistically significant and positive effect on trade flows, reinforcing the crucial role of economic growth in supporting export and import activity. Inflation, by contrast, negatively affects export competitiveness, suggesting the need for coordinated monetary stabilization. The Error Correction Model (ECM) indicates a relatively fast speed of adjustment, with 63.65% of short-term disequilibria corrected in the subsequent period. This study contributes to the limited body of applied research on North African economies by applying a dynamic modeling framework that remains underutilized in the region. The findings offer new insights into Algeria’s macroeconomic behavior under currency shocks and provide a solid empirical foundation for policy formulation. Policy implications highlight the need for a more flexible exchange rate regime, inflation-targeting strategies, and broader structural reforms to stabilize trade performance, reduce external vulnerabilities, and enhance long-term economic resilience.